HALAL REGULATION AND CERTIFICATION IN THE CATERING BUSINESS: A Critical Review of Consumer Protection - Maulidia, Rohmah; Rofi'ah, Khusniati; Santoso, Lukman (Jurisdictie: Jurnal Hukum dan Syariah, 2024)
Halal certification in catering businesses still faces various regulatory and implementation problems, which impact the lack of consumer protection rights. This article explores the implications of halal regulation and certification in the catering business for consumer protection and how the catering business sector is ready to respond to halal certification. The research method used is juridical sociological research, with an empirical approach and critical analysis of relevant literature, including legal regulations and halal certification standards, as well as case studies of catering business practices in Ponorogo. The results show that proper understanding and implementation of halal regulations and certification contribute significantly to consumer protection by creating trust, ensuring information transparency, and improving the quality and safety of the food provided. This research provides a deep insight into the relationship between halal regulation and consumer protection in the context of the catering business. It highlights the importance of legal awareness and appropriate practices for business actors, thereby supporting the success of halal certification programs in the food business sector, including catering. Sertifikasi halal pada usaha catering masih menghadapi beragam problem regulasi dan implementasi, sehingga berdampak pada minimnya hak perlindungan bagi konsumen. Artikel ini bertujuan untuk mengeksplorasi implikasi regulasi dan sertifikasi halal dalam bisnis katering terhadap perlindungan konsumen serta bagaimana kesiapan sektor usaha katering dalam menyikapi sertifikasi halal tersebut. Metode penelitian yang digunakan adalah penelitian yuridis sosiologis, dengan pendekatan empiris dan analisis kritis terhadap literatur yang relevan, termasuk peraturan hukum dan standar sertifikasi halal, serta studi kasus dari praktek bisnis katering di Ponorogo. Hasil penelitian menunjukkan bahwa pemahaman dan implementasi yang tepat terhadap regulasi dan sertifikasi halal berkontribusi secara signifikan terhadap perlindungan konsumen, dengan menciptakan kepercayaan, memastikan transparansi informasi, dan meningkatkan kualitas serta keamanan makanan yang disediakan. Kontribusi penelitian ini adalah memberikan wawasan yang mendalam tentang hubungan antara regulasi halal dan perlindungan konsumen dalam konteks bisnis katering, serta menyoroti pentingnya kesadaran hukum dan praktik yang sesuai bagi para pelaku bisnis. Sehingga menunjang keberhasilan program sertifikasi halal pada sektor bisnis makanan, termasuk katering.